Branch Efficiency Analysis with a Hybrid DEA-AHP Analysis and Distribution Channel Selection with Linear Programming Model in a Parcel Company - Sebnem Indap; Batuhan Kocaoglu (Research Developments in Science and Technology Vol. 9, 2022)
The parcel delivery sector is a rapidly growing and highly competitive business with branches and hubs as distribution channels. In recent years, increasing e-commerce volume has improved the way parcels are distributed. The success of the parcel delivery companies depends on on-time deliveries, which directly impacts customer satisfaction. Therefore, it is very important to measure the efficiency of branches that perform last-mile delivery operations. Data Envelopment Analysis (DEA) is one of the methods for efficiency measurement. Analytic Hierarchy Process (AHP) is a multiple criterion evaluation model that provides a methodology for comparing alternatives by structuring criteria into a hierarchy. Hub-and-Spoke business model is an important method for last-mile on-time delivery. Firstly, a hybrid model combining DEA and AHP was applied in order to measure branch efficiency. According to the results, for branches with low efficiency, it is proposed to apply the Hub-and-Spoke model that is direct distribution from Hubs. Secondly, in order to test the accuracy of the model, LP model was applied for the selection of the distribution channel that is the branches to stay open and the areas where Hub-and-Spoke distribution model can be applied.